Corrosion behaviour of stainless steel, nickel base alloy and titanium weldments in chlorination and chlorine dioxide bleaching - Tuthill, Arthur H.; Avery, Richard E.; Garner, Andrew (Nickel Development Institute, 1992)
This publication presents an overview of a decade-long series of programs which exposed welded coupon and full diameter pipe in chlorination and chlorine dioxide bleaching equipment. Findings have guided procedures for the fabrication and post fabrication clean-up of over 75 6% Mo stainless steel washers. Findings are also applicable to 6% Mo, nickel base alloy, clad nickel base alloy, titanium and plastic-lined piping for bleach plants. Guidelines for procurement and fabrication of piping materials are included. Applicability to mixer-to-tower, tower-to-vat and filtrate piping sections is reported.
"Reprinted with permission from Proceedings of the Technical Association of the Pulp and Paper Industry, TAPPI, 7th International Symposium on Corrosion in the Pulp and Paper Industry, Orlando, FL, 1992"
Keywords: Alloys -- Corrosion.; Bleaching industry -- Equipment and supplies -- Corrosion.; elektronické knihy; electronic books